2019
DOI: 10.1016/j.dsr2.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A nutrient limitation mosaic in the eastern tropical Indian Ocean

Abstract: The Indian Ocean accounts for about one fifth of global ocean net primary production but remains undersampled relative to other major ocean basins. The eastern tropical Indian Ocean is characterized by extremely low concentrations of both macronutrients and the micronutrient iron. We measured concentrations of dissolved and particulate trace metals (Fe, Mn, Zn, Pb) in the upper ocean along the GO-SHIP IO9N transect (28˚S to 17˚N, mostly along the 95˚E meridian) during a cruise in April 2016. Cellular quotas (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 79 publications
(123 reference statements)
10
44
0
Order By: Relevance
“…Thus, severe Fe stress may be transient or seasonal in this region (Wiggert et al ; Behrenfeld et al ). Our sequence‐based findings are supported by nutrient addition incubation results from the same transect, which found evidence for Fe and N colimitation of planktonic communities but not classical iron limitation (Twining et al ). Overall, the distribution of ecotypes did not support the three‐biome hypothesis for the Eastern Indian Ocean.…”
Section: Resultssupporting
confidence: 81%
“…Thus, severe Fe stress may be transient or seasonal in this region (Wiggert et al ; Behrenfeld et al ). Our sequence‐based findings are supported by nutrient addition incubation results from the same transect, which found evidence for Fe and N colimitation of planktonic communities but not classical iron limitation (Twining et al ). Overall, the distribution of ecotypes did not support the three‐biome hypothesis for the Eastern Indian Ocean.…”
Section: Resultssupporting
confidence: 81%
“…In the surveyed areas, the surface N and the P levels were <1.0 and 0.10 µM (data not shown), with the N:P ratio being lower than 16, indicating a nitrogen limitation (Li et al, 2012a), especially in the southern Indian Ocean (Wilcoxon test, p < 0.05), where Chla biomass and picocells abundance were lower. Such a biomass variation could also be attributed by the spatial changes of trace mental iron (Chinni et al, 2019;Twining et al, 2019) that is often believed to regulate phytoplankton growth and has been observed to covary with Chla (Chinni et al, 2019;Sherman et al, 2020). On the other hand, the spatial variation in Chla was less in the DCM layer; it could be explained by the high nutrients that may be enough to support the growth of phytoplankton.…”
Section: Discussionmentioning
confidence: 98%
“…The organic speciation of Cu may control its bioavailability to phytoplankton. Because of its important physiological role (e.g., for iron, oxygen, and nitrogen cycling; Granger & Ward, 2003;La Fontaine et al, 2002;Maldonado et al, 2006;Merchant & Helmann, 2012), Cu is required in phytoplankton cells in proportions varying on average between 0.4 and 2 mmol:mol relative to P and up to 3 mmolCu:molP (Twining & Baines, 2013;Twining et al, 2019). The most bioavailable form of copper for phytoplankton is Cu', but the very low concentrations in surface seawater may indicate that insufficient Cu' is available to meet phytoplankton requirements.…”
Section: Introductionmentioning
confidence: 99%